Investigation of Boldine as a Potential Telomerase Inhibitor by Downregulation of hTERT/hTERC in HCT 116 Human Colon Carcinoma Cells - Ahmad, Nadhirah (Penerbit Universiti Kebangsaan Malaysia, 2019)
Telomerase, a ribonucleoprotein (RNP) complex, is a type of RNA-dependent DNA polymerase that synthesises telomeric DNA repeats (TTAGGG) at the 3' end of chromosomes. Most of the cancer cells express high level of telomerase which results in cellular immortality. The high telomerase activity in cancer cells can be detected via expression of human TERT (hTERT), the catalytic protein subunit of telomerase, and expression of human TERC (hTERC), the RNA component in telomerase. Boldine, a natural alkaloid compound, was shown to have anticancer properties on various types of cancer cells, but the anti-telomerase property was poorly understood. This study was carried out to investigate the ability of boldine in targeting telomerase on the human colon cancer cell line, HCT 116, by analyzing the expression of hTERT and hTERC. Boldine was shown to have a time- and dose-dependent cytotoxic effect on HCT 116 cell line in SRB assay. The protein expression of hTERT was assessed through Western blot where it was observed to be down-regulated upon boldine treatment compared to control. The cells treated with boldine also exhibited a down-regulation of mRNA expression for both hTERT and hTERC in Real Time PCR (qRT-PCR). The down-regulation of hTERT protein expression correlated with the reduced hTERC mRNA expression in qRT-PCR. The observations on the down-regulation of protein and mRNA expressions of telomerase related genes, hTERT and hTERC, in this study suggested that boldine might become a significant candidate for telomerase-targeted anti-cancer therapy. © 2019 Penerbit Universiti Kebangsaan Malaysia. All rights reserved.